Trade openness and economic growth: empirical evidence from India - Hye, Qazi Muhammad Adnan; Lau, Wee-Yeap (Journal of Business Economics and Management, 2014)
The main objective of this study is to develop first time trade openness index and use this index to examine the link between trade openness and economic growth in case of India. This study employs a new endogenous growth model for theoretical support, auto-regressive distributive lag model and rolling window regression method in order to determine long run and short run association between trade openness and economic growth. Further granger causality test is used to determine the long run and short run causal direction. The results reveal that human capital and physical capital are positively related to economic growth in the long run. On the other hand, trade openness index negatively impacts on economic growth in the long run. The new evidence is provided by the rolling window regression results i.e. the impact of trade openness index on economic growth is not stable throughout the sample. In the short run trade openness index is positively related to economic growth. The result of granger causality test confirms the validity of trade openness-led growth and human capital-led growth hypothesis in the short run and long run.